The Effectiveness of Using Application English Conversation Practice to Teach Speaking in SMPN 1 Tembelang Jombang - Haviza Ainun Nadziva; Maskhurin Fajarina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research aims to find out the empirical evidence of the effectiveness of using English Conversation Practice application to teach speaking. In this research, the quantitive method was used and the research design was a pre experimental design in the form of one group pretest-posttest which consisted of five meetings include the treatments. To conduct the research, 31 students of class VIII I of SMPN 1 Tembelang Jombang in the academic year of 2021/2022 are choosen as the sample. In this class consisted of 17 male and 14 female students so the researcher used the purposive sampling technique and the instrument used were speaking test. Based on the calculation, the mean scores of pre-test was 23.35 and the mean scores of posttest was 39.35. The result of statistical hypothesis testing by using paired sample t-test and the researcher finds that tobserve was higher than ttable (6.928 < 2.042). Therefore, the alternative hypothesis (Ha ) was accepted and null hypothesis (Ho) was rejected. The result indicated that using English conversation practice application is effective to teach speaking in class VIII I of SMPN 1 Tembelang Jombang in the academic year 2021/2022.